Safety system design and overfill protection for loading asphalt onto trucks. Issue 4 (26th March 2022) - Ampadu, Wendy; Malik, Hassan; Diezmos, Ray; Hyslob, Jeremy
Abstract: There are several technologies out there for use as high‐level switches as part of a system for shutting down flow to a vessel. Given that asphalt truck loading poses issues such as poor visibility, coating, condensation, and fumes, a solution that is robust enough to last in these conditions is often needed in industries. Furthermore, the design of the loading arm, rack, and process equipment may need to be changed to allow for the safety to work as needed. This report would not just be selecting an overflow technology but completing the redesign of structures for use at loading facilities. This report is based on loading facilities at a bitumen production company based in Toronto, Canada with over 25 locations across the country. The engineering design approach was used to create multiple redesign concepts for the loading dock system. Research on overfill systems was also completed by surveying the existing market for technologies and securing quotes from over 20 Canadian and United States instrumentation companies. A final loading dock redesign and level transmitter for overfill protection solution were chosen.